SYSTEMATIC LITERATURE REVIEW: SISTEM INFORMASI MANAJEMEN PENGARSIPAN SECARA DIGITAL - Mohamad Firdaus Fitrananda; Ines Heidiani Ikasari (Shofanah Media Berkah, 2023)
Archive Management Information System digitally is a modern solution for managing and storing archival documents. In the era of growing digitalization, the use of a filing management information system is important to optimize efficiency and security in managing records. This study aims to design and implement a digital filing management information system that can facilitate the process of archiving, searching, and maintaining archival documents more effectively and efficiently. The research method used is the waterfall approach, starting from the analysis of user needs, system design, development, testing, to implementation. The information system developed uses the latest technology and is web-based to facilitate access and use from various devices. The main features in this system include document classification and category management, keyword-based search, document preview display, integration with security systems, and monitoring and reporting of user activity. In testing the system, functionality tests, search speed, data security, and user satisfaction are tested. The test results show that this digital filing management information system provides convenience in the filing process, faster document search, and guaranteed security. In implementing the system, training is carried out for users so they can operate the system properly. Within a certain period of time, users provide positive feedback regarding increased efficiency and productivity in managing records. Thus, this digital filing management information system has the potential to increase efficiency and security in managing records. The use of the latest technology in this system allows easy access, fast document search, and effective maintenance. The implication of this research is that the use of a digital filing management information system can be a relevant solution in increasing the efficiency and effectiveness of records management in various organizations.